Pendidikan Kesehatan Tentang Nutrisi Ibu Hamil di Puskesmas Krueng Barona Jaya - Cut Oktaviyana; Syarifah Masthura (STIKes Ibnu Sina Ajibarang, 2024)
Nutrition is important for both the mother and the fetus during pregnancy. A healthy pregnancy requires a good diet to prevent problems for the mother and fetus during the first 1,000 days of the baby's life. One way to improve the health of pregnant women is to provide them with health education related to nutrition. The goal is to improve understanding of nutrition for a healthy pregnancy and optimal fetal growth and development. The method used was lectures and discussions with three pregnant women who participated in the activity. The result of this activity was an increase in knowledge, as evidenced by the fact that 90% of the questions on the post-test were answered correctly, compared to 60-70% on the pre-test. Therefore, it can be concluded that the participants' knowledge increased during the health education activity.